Immunocytochemical ultrastructural analysis of chromatophore membrane formation in Rhodospirillum rubrum. - Crook, S M (1986)
An immunocytochemical ultrastructural study of Rhodospirillum rubrum cultured under semiaerobic conditions was conducted to correlate the localization of functional components with membrane formation. R. rubrum is a facultatively phototrophic organism. Under reduced oxygen, this bacterium forms an intracytoplasmic chromatophore membrane that is the site of the photosynthetic apparatus. Immunogold techniques were used to localize intracellular protein antigens associated with the photosynthetic apparatus. Antibody, demonstrated by immunoblotting to be specific for the reaction center and light-harvesting photochemical components, was conjugated to colloidal gold particles and used for direct immunolabeling of fixed, sectioned specimens. Membrane invaginations appeared by 4 h after transition to induction conditions, and mature chromatophore membrane was abundant by 22 h. The occurrence of chromatophore membrane was correlated with bacteriochlorophyll a content and the density of the immunolabel. In uninduced (aerobic) cells and those obtained from cultures 0.5 h posttransition, the immunogold preferentially labeled the peripheral area of the cell. In contrast, in cells obtained after 22 h of induction, the central region of the cell was preferentially immunolabeled. These findings provided immunocytochemical evidence supporting the hypothesis that the chromatophore membrane is formed by invagination of the cytoplasmic membrane.